Intuitive data and image analysis about the microstructure of the liquid alumina system - Lan, Mai Thi; Nguyen Thi Thanh Ha; Nguyen Thu Nhan; Nguyen Van Hong (Vietnam Journal of Science and Technology, 2024)
The models of the Al2O3 system in a liquid state over broad ranges of pressure from 0 to 100 GPa are built by molecular dynamics simulation (MDs). This research gives useful knowledge about the microstructural properties of liquid alumina systems through insight 3D visualization. Intuitive data and image analysis methods are applied to clarify the network structure, the local environment of Al and O atoms, and the linkage among the polyhedra in the network structure of the Al2O3 system at different pressure. The structural compaction mechanism of Al2O3 oxides under high pressure is also discussed in this paper.